Timber Trading Trends in Madhya Pradesh - Argal, Akhilesh; Berry, Nanita; Sood, L. K.; Chawdhry, P. K.; Shukla, P. K. (Indian Forester, 2003)
This paper analyzes market price variation of seven timber species in M.P. over a period of about 20 years. The auction result data for major timber depots of Central Circle, Jabalpur, M.P.) are the basis of analysis. The analysis shows that the prices of major timber spp., viz. Teak, Sal, Bija, Haldu, Saja, Dhawa and Salai have increased over the year. The increase was about 40% to 45% dnring 1987.88 to 1990.91. During 1990-91 to 1995-96 increase was about 85% to 100%, whereas during 1995-96 to 2000-01, the increase was comparatively less (0 to 25%). The comparatively less increase in price during 1995.96 to 2000-2001 may be attributed to import of timber from Nigeria, Ghana, Burma, Malaysia; on account of large scale felling of Sal trees during 1998.99 and also due to general slack is economy.